KANDUNGAN NITRAT DAUN, PERTUMBUHAN, DAN HASIL BIOMASSA SAWI DAN PAKCOY PADA PEMBERIAN PUPUK NITROGEN ANORGANIK DAN KOMPOS AZOLLA SECARA BERIMBANG - Pratiwi Pratiwi; Marwanto Marwanto; Widodo Widodo; Merakati Handajaningsih (BPFP Universitas Bengkulu, 2021)
[LEAF NITRATE CONTENT, GROWTH, AND BIOMASS YIELD OF GREEN MUSTARD AND CHINESE CABBAGE FOLLOWING BALANCED APPLICATION OF INORGANIC NITROGEN FERTILIZER AND AZOLLA COMPOST]. The aim of this study was to determine the application rate of Azolla compost, either alone or combined with inorganic N fertilizers, to produce high biomass of mustard greens and Chinese cabbage with low leaf nitrate content. The pot experiments were carried out at the Research Plot of the Faculty of Agriculture located in Bengkulu University Campus from December 2019 to January 2020 with five treatments arranged in a completely randomized design with five replications. The treatments were 100% IF or IF100 (42.0 mg N/kg soil), 100% AC or AC100 (4000 mg/kg soil), IF75 (31.0 mg N/kg soil) + AC25 (1000 mg/kg soil), IF50 (21.0 mg/kg soil) + AC50 (2000 mg/kg soil), and IF25 (10.5 mg/kg soil) +AC75 (3000 mg/kg soil). The results showed that partial replacement of IF with AC (IF75 +AC25) produced plant growth and biomass yield similar to IF100 or higher than IF100 and AC100. The treatment produced plant biomass of 9.35 g plant-1 for green mustard and 167.10 g plant-1 for pakcoy, 32% and 35% higher than AC100 treatment respectively. The leaf nitrate content was 1080 - 2760 mg kg-1 for green mustard and 2310 - 2820 mg kg-1for Chinese cabbage, lower than the maximum limit of safe nitrate for consumption which was set at 3100 mg kg-1. Overall, compared with their sole applications, the partial substitution of inorganic N fertilizer with Azolla compost represents the most effective practice to promote the biomass yield of low-nitrate green mustard and Chinese cabbage.